Portuguese recommendations for the use of biological therapies in patients with axial spondyloarthritis -- 2016 update. - Machado, P. M.; Cerqueira, M.; Ávila-Ribeiro, P.; Aguiar, R.; Bernardo, A.; Sepriano, A.; Águeda, A.; Cordeiro, A.; Raposo, A.; Rodrigues, A. M.; Barcelos, A.; Malcata, A.; et al. (Acta Reumatológica Portuguesa)
Objective: To update the recommendations for the treatment of axial spondyloarthritis (axSpA) with biological therapies, endorsed by the Portuguese Society of Rheumatology. Methods: These treatment recommendations were formulated by Portuguese rheumatologists based on literature evidence and consensus opinion. At a national meeting, the recommendations included in this document were discussed and updated. A draft of the full text of the recommendations was then circulated and suggestions were incorporated. A final version was again circulated before publication and the level of agreement among Portuguese Rheumatologists was anonymously assessed using an online survey. Results: A consensus was achieved regarding the initiation, assessment of response and switching of biological therapies in patients with axSpA. In total, se ven recommendations were produced. The first recommendation is a general statement indicating that biological therapy is not a first-line drug treatment option and should only be used after conventional treatment has failed. The second recommendation is also a general statement about the broad concept of axSpA adopted by these recommendations that includes both non-radiographic and radiographic axSpA. Recommendations 3 to 7 deal with the definition of active disease (including the recommended threshold of 2.1 for the Ankylosing Spondylitis Disease Activity Score [ASDAS] or the threshold of 4 [0-10 scale] for the Bath Ankylosing Spondylitis Disease Activity Index [BASDAI]), conventional treatment failure (nonsteroidal anti-inflammatory drugs being the first-line drug treatment), assessment of response to treatment (based on an ASDAS improvement of at least 1.1 units or a BASDAI improvement of at least 2 units [0-10 scale] or at least 50%), and strategy in the presence of an inadequate response (where switching is recommended) or in the presence of long-term remission (where a process of biological therapy optimization can be considered, either a gradual increase in the interval between doses or a decrease of each dose of the biological therapy). Conclusion: These recommendations may be used for guidance in deciding which patients with axSpA should be treated with biological therapies. They cover a rapidly evolving area of therapeutic intervention. As more evidence becomes available and more biological therapies are licensed, these recommendations will have to be updated.